TransCom continuous experiment: comparison of 222Rn transport at hourly time scales at three stations in Germany - Taguchi, Shoichi; Law, R. M.; Rödenbeck, Christian; Patra, Prabir K.; Maksyutov, Shamil; Zahorowski, W.; Sartorius, Hartmut; Levin, Ingeborg (Atmospheric chemistry and physics, 2011)
Abstract. Fourteen global atmospheric transport models were evaluated by comparing the simulation of 222Rn against measurements at three continental stations in Germany: Heidelberg, Freiburg and Schauinsland. Hourly concentrations simulated by the models using a common 222Rn-flux without temporal variations were investigated for 2002 and 2003. We found that the mean simulated concentrations in Heidelberg are related to the diurnal amplitude of boundary layer height in each model. Summer mean concentrations simulated by individual models were negatively correlated with the seasonal mean of diurnal amplitude of boundary layer height, while in winter the correlation was positive. We also found that the correlations between simulated and measured concentrations at Schauinsland were higher when the simulated concentrations were interpolated to the station altitude in most models. Temporal variations of the mismatch between simulated and measured concentrations suggest that there are significant interannual variations in the 222Rn exhalation rate in this region. We found that the local inversion layer during daytime in summer in Freiburg has a significant effect on 222Rn concentrations. We recommend Freiburg concentrations for validation of models that resolve local stable layers and those at Heidelberg for models without this capability.